2021
DOI: 10.1029/2020gb006718
|View full text |Cite
|
Sign up to set email alerts
|

Global Estimates of Marine Gross Primary Production Based on Machine Learning Upscaling of Field Observations

Abstract: Approximately half of global primary production occurs in the ocean. While the large-scale variability in net primary production (NPP) has been extensively studied, ocean gross primary production (GPP) has thus far received less attention. In this study, we derived two satellite-based GPP models by training machine learning algorithms (Random Forest) with light-dark bottle incubations (GPP LD) and the triple isotopes of dissolved oxygen (GPP 17Δ). The two algorithms predict global GPPs of 9.2 ± 1.3 × 10 15 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 101 publications
5
16
0
Order By: Relevance
“…Machine learning (ML) methods are rapidly gaining interest across the geosciences for their adaptability and ability to capture complex relationships without prior knowledge of underpinning mechanisms (Li et al, 2016;Mattei et al, 2018;Rafter et al, 2019;Tang et al, 2019;Wang et al, 2020;Chen et al, 2020;Huang et al, 2021). In addition to being used to evaluate biogeochemical models, they can also be used to guide sampling strategies, and infer mechanisms through statistical inferences (Li and Cassar, 2016;Roshan and DeVries, 2017;Mattei et al, 2018;Chen et al, 2020;Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) methods are rapidly gaining interest across the geosciences for their adaptability and ability to capture complex relationships without prior knowledge of underpinning mechanisms (Li et al, 2016;Mattei et al, 2018;Rafter et al, 2019;Tang et al, 2019;Wang et al, 2020;Chen et al, 2020;Huang et al, 2021). In addition to being used to evaluate biogeochemical models, they can also be used to guide sampling strategies, and infer mechanisms through statistical inferences (Li and Cassar, 2016;Roshan and DeVries, 2017;Mattei et al, 2018;Chen et al, 2020;Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [3,57,58] demonstrated that upscaling the field GPP through machine learning methods was also a good way to make the field GPP comparable with remote sensing products. However, the uncertainties and error transfers in the upscaling process are still not very clear [59].…”
Section: Scale Mismatching Between Satellte Gpp and Ground Observed Gppmentioning
confidence: 99%
“…Algae are a heterogenous group of photosynthetic, oxygen-producing, mostly aquatic organisms, that lack the complexity of a typical plant structure (leaves, stem, roots and complex reproductive structures). These simple organisms are critically important; it is estimated that 50-80% of the oxygen produced on Earth originates from algae and about half of the global total annual productivity is carried out by algae in the oceans [1,2]. Furthermore, algae influence climate by controlling processes such as biogenic calcification, oceanic sequestration of CO 2 and release of dimethylsulfide [3], along with the production of a wide array of natural compounds that play a primary role in ecosystem functioning and influence the environment and surrounding organisms [4], thus fulfilling very important ecosystem services.…”
Section: General Introduction To Algaementioning
confidence: 99%